Reversal of drug resistance by planetary ball milled (PBM) nanoparticle loaded with resveratrol and docetaxel in prostate cancer. (28th July 2018) - Singh, Santosh Kumar; Lillard, James W.; Singh, Rajesh
Abstract: The folate receptor (FR) is a valued target that is highly expressed in various cancers, which will expedite the development of ligand-receptor binding based cancer therapeutics. In the present investigation, through tissue microarray analysis, we report higher levels of folate receptor expression in prostate cancer (PCa) tissue derived from patients, which were minimal in normal tissue. For folate-receptor based targeted therapy of PCa, we generated novel planetary ball milled (PBM) nanoparticles (NPs) encapsulated with resveratrol (RES), and in combination with docetaxel (DTX) and conjugated with folic acid (FA) on the surface. The cytotoxic effect of FA-conjugated DTX-nanoparticles was found effectual that reduced the concentration of free drug (DTX) to 28 times. Flow cytometry analysis showed a significant increase in the number of apoptotic cells by 30.92% and 65.9% in the FA-conjugated RES and in combination with DTX nanoparticle formulation respectively. However, only 8.9% apoptotic cells were found with control (empty NP). The expressions of NF-kB p65, COX-2, pro (BAX, BAK) and anti-apoptotic (BCL-2, BCL-XL) genes were significantly reduced after treatment with FA-RES + DTX-NP. In addition, the FA-conjugated DTX formulation exhibited additional cytotoxic effects with the down-regulation of survivin and an increased expression of Cleaved Caspase-3 in PCa cells. Further, we observed that treating DTX resistant PCa cells with FA-RES + DTX-NP exhibited a reversal of the ABC -transporter markers thereby limiting the multidrug resistance phenotype of the cancer cells. Our results strongly suggested that FA conjugated nanoparticle drugs acted as effective inhibitors of drug efflux that effectually enhances the intracellular concentration of the drug to exhibit their cytotoxic effect. Highlights: Clinical samples of prostate cancer (PCa) express higher levels of folate receptor. Docetaxel resistance prostate cancer cells overexpress folate receptor and ATP-binding cassette transporters. Folic acid conjugated resveratrol and docetaxel nanoparticles downregulate BCL-2, BCL-XL and survivin while inducing BAX, BAK, and Caspase-3. Folic acid nanoparticle drugs are recommended for treating docetaxel resistance PCa.